Genetic Identification of a High-Affinity Ni Transporter and the Transcriptional Response to Ni Deprivation in Synechococcus sp. Strain WH8102 - Dupont, C. L. (American Society for Microbiology, 2012)
One biological need for Ni in marine cyanobacteria stems from the utilization of the Ni metalloenzyme urease for the assimilation of urea as a nitrogen source. In many of the same cyanobacteria, including Synechococcus sp. strain WH8102, an additional and obligate nutrient requirement for Ni results from usage of a Ni superoxide dismutase (Ni-SOD), which is encoded by sodN. To better understand the effects of Ni deprivation on WH8102, parallel microarray-based analysis of gene expression and gene knockout experiments were conducted. The global transcriptional response to Ni deprivation depends upon the nitrogen source provided for growth; fewer than 1% of differentially expressed genes for Ni deprivation on ammonium or urea were concordantly expressed. Surprisingly, genes for putative Ni transporters, including one colocalized on the genome with sodN, sodT, were not induced despite an increase in Ni transport. Knockouts of the putative Ni transporter gene sodT appeared to be lethal in WH8102, so the genes for sodT and sodN in WH8102 were interrupted with the gene for Fe-SOD, sodB, and its promoter from Synechococcus sp. strain WH7803. The sodT::sodB exconjugants were unable to grow at low Ni concentrations, confirming that SodT is a Ni transporter. The sodN::sodB exconjugants displayed higher growth rates at low Ni concentrations than did the wild type, presumably due to a relaxed competition between urease and Ni-SOD for Ni. Both sodT::sodB and sodN::sodB lines exhibited an impaired ability to grow at low Fe concentrations. We propose a posttranslational allosteric SodT regulation involving the binding of Ni to a histidine-rich intracellular protein loop.